COST STRUCTURE AND INVESTMENT ANALYSIS OF SHEEP ENTERPRISE IN CHITTOOR DISTRICT OF ANDHRA PRADESH (Indian Journal of Animal Production and Management, 2015)
A survey was conducted with a sample of 38 sheep beneficiaries of Rashtriya Krishi Vikas Yojana (RKVY) in Chittoor District of Andhra Pradesh. Cost structure and investment analysis have been worked out in sheep rearing among the RKVY beneficiaries. The total cost per unit (20 ewes + 1 ram) was estimated as Rs.1,03,024.32, Rs.73,256.26 and Rs.66,909.04 for the first, second and third years, respectively. Net returns per unit were Rs.9157, Rs. 18,222 and Rs.29,056 for the aforesaid years, respectively. The returns per rupee of expenditure tended to increase from 1.09 in the first year to 1.43 in the third year. NPW at 12 per cent rate was Rs.1,43,220 while the Benefit cost ratio was 1.23. The senstivity analysis indicated that the enterprise was economically viable even at 24% discount rate.
Keywords: Total Costs; Variable costs; Fixed costs; Benefit-Cost ratio